Virulence of Escherichia coli in experimental hematogenous pyelonephritis in mice. - van den Bosch, J F (1979)
Differences in nephropathogenicity between Escherichia coli strains were studied by following the kinetics of the viable count in the mouse kidney during 8 h after intravenous injection. Assuming as a reference point that at zero time 0.1% of the inoculum was lodged in the kidney, we found that strains fell into three main groups with different behavior patterns: in group I, the viable count fell and remained low; in group II, the viable count first fell and then rose after 4 h, reaching the level of the reference point within 8 h; in group III, the viable count rose rapidly and remained high. The kinetics of the viable counts were also studied in blood, spleen, and liver: group I and II strains behaved similarly; only in the kidney did group II strains show higher counts than group I strains. These data suggest that group II strains are specifically virulent for the mouse kidney. Group III strains also gave higher viable counts in blood and spleen but comparable counts in the liver, suggesting that group III strains are more generally virulent. Fifty percent lethal dose measurements confirmed the conclusion that group I strains are avirulent and group III strains are the most virulent. Possible relationships between behavior pattern and serotype are discussed.